Evaluation of yellow pumpkin seed extract (Cucurbita moschata D) on the successful masculinization of betta fish (Betta splendens) - Fadhilah, Sari Nur; Lestari, Tuti Puji; Farida, Farida (Acta Aquatica: Aquatic Sciences Journal, 2023)
Betta fish is one of the most popular freshwater ornamental fish. This ornamental fish is very popular among people of various ages because it is easy to maintain. However, fans of these ornamental fish prefer male fish over females because male fish have aesthetic values and better and attractive colors and have higher profits. The experiment aims to determine the effect of yellow pumpkin seed extract on the successful of male betta fish larvae, as well as giving the best dose. The design used was a completely randomized design (CRD) with 4 treatments and 3 replications. The immersion doses used were control A, treatment B with a dose of 40 mg/L, treatment C with a dose of 80 mg/L and treatment D with a dose of 120 mg/L. Maintenance period for 30 days. The results showed that soaking using yellow pumpkin seed extract with different concentrations had a very significant effect on the percentage of males. The percentage of male betta fish ranged from 40.00-90.00%, the percentage of female betta fish ranged from 5.00-45.00%, and the percentage of intersex betta fish ranged from 5.00-15.00%. The best concentration of yellow pumpkin seed extract was 120 mg/L with the percentage of male betta fish 90.00% in treatment D.Keywords: Betta splendens Larvae; Immersion; Maleization; Pumpkin Seed Extract